Association Between Maternal Preeclampsia and Neonatal Asphyxia: A Cross-Sectional Study in a Referral Hospital in Lampung, Indonesia - Lestari, Muji; Dahliana, Maya Dika; Sari, Gita Nirmala (Universitas Andalas, 2025)
Preeclampsia is a significant contributor to neonatal complications, particularly neonatal asphyxia, which remains one of the leading causes of early neonatal mortality. This study aimed to determine the association between maternal preeclampsia and neonatal asphyxia and to examine the modifying effects of maternal age and parity. A retrospective cross-sectional study was conducted at a referral hospital in Lampung Province using secondary data from 96 laboring mothers and their newborns in 2024. Preeclampsia was identified based on clinical diagnosis, and neonatal asphyxia was defined by a 1-minute Apgar score below 7. Chi-square test and multivariable logistic regression were used for statistical analysis. The results showed that 62.5% of mothers were diagnosed with preeclampsia, and 43.8% of newborns experienced neonatal asphyxia. A significant association was found between preeclampsia and neonatal asphyxia, with an adjusted odds ratio (OR) of 3.14 (95% CI: 1.29–7.61; p = 0.011). Interaction analysis indicated that maternal age under 20 years (adjusted OR = 4.25; p = 0.039) and primiparity (adjusted OR = 3.78; p = 0.027) significantly increased the risk of neonatal asphyxia among mothers with preeclampsia. These findings highlight the compounded risks in younger and first-time mothers with hypertensive disorders of pregnancy. This study underscores the importance of early detection of preeclampsia, tailored antenatal care, and close monitoring of high-risk pregnancies, particularly among adolescents and primiparous women, to prevent adverse neonatal outcomes such as asphyxia